Monologen der blev væk. Herman Bangs “Efter Ballet” genfundet - Jürgensen, Knud Arne (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Herman Bang’s reputation as one of our greatest impressionist fiction writers is now undisputed. The assessment of his work as a playwright, on the other hand, is more complicated. This might seem surprising considering that Bang in particular, more than so many other writers, was a master at describing and “delineating” his fellow human beings by means of what they said and how they expressed themselves. Over the years Bang wrote a total of 14 plays and lesser theatrical works plus three translations of plays, all of which, with two exceptions, were performed at the leading Danish and Scandinavian theatres of the day, with a single work also being staged in Paris. None of these works was a conclusive success with either the public or the critics, however. The exception may be the recently discovered monologue entitled “Efter Ballet” (After the Ball), which Bang wrote in the summer of 1880. It represents one of his earliest public appearances as a playwright and was written for Betty Borchsenius (1850-90), one of the leading actresses of the day, who was very close to him at this time and whom he directed in both his own and other people’s dramatic works on several occasions. Bang referred to this monologue as one of his best and happiest pieces of work for the theatre in a number of contexts. The manuscript for “Efter Ballet” that has now been rediscovered in all probability represents the author’s own personal director’s copy, as it contains underlinings of the monologue’s many interesting stage directions and a number of linguistic corrections made by Bang himself. The manuscript’s highly significant directions regarding the principal character’s movements on stage are characteristic of Herman Bang the director. Even in this early work it is possible, for example, to trace the striving towards a theatrical naturalism that Bang worked so tirelessly to achieve in his lifelong activities as a director. The article introduces this hitherto unpublished piece of drama and also reprints an extended biographical essay he wrote about the monologue’s interpreter.